Violence in lesbian relationships: barriers to seeking help in Catalonia (Simbiótica. Revista Eletrônica, 2026)
The objective of this study is to identify the obstacles faced by lesbian women who are victims of intimate partner violence when seeking help, from a feminist perspective.  We conducted a non-experimental cross-cutting study using a self-administered questionnaire, using a convenience sample and snowball technique. Of the 128 women who took part, 83 said they were or had been victims. Among the participants who did not initiate the process of seeking help, there were various psychological, social, and legal barriers. The results not only contribute to raising awareness of the phenomenon but also promote the implementation of public policies aimed at improving the resources available for care, support, and assistance to victims, facilitating the processes of de-victimization. This study identifies limitations and makes recommendations for future research.
Keywords: Intimate partner violence; lesbian women; help-seeking; barriers